Produktivitas dosen UIN Syarif Hidayatullah Jakarta pada jurnal terindeks Scopus: suatu kajian bibliometrik - Nurul Hayati; Lolytasari Lolytasari (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2017)
This study measures the productivity of UIN Jakarta lecturers’ authorship in Scopus indexed journal, by calculating and analyzing the number of published scientific papers, collaboration level and collaboration index, and lecturer productivity of UIN Jakarta under Lotka Law. The research method used is descriptive research with quantitative approach. Data analysis was done by bibliometric study. The results showed that there are 447 scientific works written by 114 lecturers of UIN Jakarta has been published in Scopus indexed journal during the period of 2002 - July 2017. The degree of collaboration of UIN Jakarta lecturers in writing scientific papers is 0.74, while the lecturer collaboration index UIN lecturer Jakarta in writing scientific paper is 0.255. Based on Lotka’s Law, the sole authorship of UIN Jakarta lecturers in Scopus indexed journals only resulted in 0.034 (3%) of the overall publication results. Thus it can be concluded that the productivity of UIN Jakarta lecturers in producing fewer individual scien-tific works than in collaboration.